Lorentz Transformations and the Theory of Relativity: A Fundamental Concept - Tehrani , Fleur T. (Fundamental Research and Application of Physical Science Vol. 4, 2023)
The purpose of this research was to get an in depth understanding of Lorentz transformations and the theory of relativity. The foundations of the relativistic concepts of space and time, their connections to Lorentz transformations, and the equivalence of mass and energy were investigated as part of a research study on Lorentz transformations and the theory of relativity. Numerous references on the aforementioned topics were examined. Lorentz transformations are empirical; the concept of contraction of space in a moving coordinate system as viewed by a stationary observer can be derived from Lorentz transformations. However, some critical questions have risen in the course of this research study on the concept of dilation of time in a moving system as measured by a stationary observer, and the concept of unbounded increase of a particle’s mass with velocity.